Regional Development in Central-Eastern European Countries at the Beginning of the 21st Century: Path Dependence and Effects of EU Cohesion Policy - Dyba, Wojciech; Loewen, Bradley; Looga, Jaan; Zdražil, Pavel (Quaestiones Geographicae, 2018)
Cohesion Policy has provided new impulses for development in Central and Eastern European Countries (CEECs) that continue to be challenged by regional disparities. This paper investigates the effects of the European Union Cohesion Policy on regional development. After presenting historical development patterns of the investigated area and opportunities afforded by this policy, its effects on a variety of indicators are analysed for the period 2007–2014. The analysis allowed confirming positive effects of EU Cohesion Policy on the development of CEE regions. However, these effects differ across the investigated area. Moving forward, it will be crucial to develop institutions and policies characteristic to each region that are stable and efficient without external funds.